2012
DOI: 10.1523/jneurosci.2247-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multiple Exon 1 Variants in Mammalian HuD mRNA and Neuron-Specific Transcriptional Control via Neurogenin 2

Abstract: The RBP (RNA-binding protein) and Hu/ELAV family member HuD regulates mRNA metabolism of genes directly or indirectly involved in neuronal differentiation, learning and memory, and several neurological diseases. Given the important functions of HuD in a variety of processes, we set out to determine the mechanisms that promote HuD mRNA expression in neurons using a mouse model. Through several complementary approaches, we determined that the abundance of HuD mRNA is predominantly under transcriptional control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…In WT NSCs, HuD mRNA expression levels increased during neuronal differentiation (SI Appendix, Fig. S5 A and B), consistent with previous findings in cell lines (15,23). We then found that HuD KO NSCs differentiated into fewer Tuj1 + neurons ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In WT NSCs, HuD mRNA expression levels increased during neuronal differentiation (SI Appendix, Fig. S5 A and B), consistent with previous findings in cell lines (15,23). We then found that HuD KO NSCs differentiated into fewer Tuj1 + neurons ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…5D). This result is consistent with the earlier finding that a ∼400-bp sequence between −1002 and −606 is responsible for transcriptional activation of the HuD E1c variant during neuronal differentiation (15).…”
Section: Satb1supporting
confidence: 93%
See 3 more Smart Citations